“Depends on Who I'm Writing To”—The Influence of Addressees and Personality Traits on the Use of Emoji and Emoticons, and Related Implications for Forensic Authorship Analysis - Marko, Karoline (Frontiers in Communication, 2022)
Converging towards or diverging from an interlocutor’s speaking style (i.e., linguistic accommodation) has been investigated in many previous studies and is a highly relevant phenomenon in forensic authorship analysis. Accommodation has also been linked to personality traits, but there is still a lack of investigations of accommodation in computer-mediated communication. The present study thus aims at examining in how far emoji use is subject to accommodation in casual online interactions, and how reliable both emoji and emoticons are as markers of authorship. Further, this study is interested in finding out about connections between both emoji and emoticon use and the Big Five personality traits of agreeableness, emotional stability, conscientiousness, openness to experiences, and extraversion. The results of the analysis show that the frequency of emoji use is indeed strongly influenced by conversation partners, and that both emoji and emoticon use correlate particularly with extraversion and agreeableness. It can further be shown that emoji and emoticons are both valuable markers of authorship to different degrees, which warrants further analyses.